Bioproduction of styrene from renewable feedstocks using ionic liquids as solvents for in situ product removal - Zapata Hendriquez, Patricio Alfredo (2019)
Styrene is a large volume commodity chemical which is used as a precursor for a diverse range of useful polymers and co-polymers. The conventional styrene synthesis is performed through dehydrogenation of petroleum-derived ethylbenzene, an energy intensive process. Its natural production has been identified in a few organisms, but extraction efficiency is very low. Microbial fermentation for the synthesis of styrene from renewable resources has been previously developed, but styrene inhibits bacterial growth at very low concentration, therefore styrene must be removed in situ, whilst the fermentation is being carried out, to an extractant organic phase. The conventional solvents generally used to generate a biphasic system exhibit volatile and flammable characteristics, making them hazardous when used in industrial large-scale processes and are usually toxic towards the biocatalysts. Therefore, it is of great interest to find non-toxic alternatives with high extraction capacity. Room temperature ionic liquids have arisen as potential alternatives due to their exceptionally manipulability, making possible to design almost infinite possible useful combinations of cation and anion. The possibility to tune their physical and chemical properties by altering functional groups or through selection of the cation and anion, allow ionic liquids to match the specific requirements of a biological system whilst also providing low toxicities. In this thesis, the potential use of ionic liquids as alternatives to traditional organic solvents for the extraction of styrene from the culture media during its biocatalytic production was investigated. A wide range of ionic liquids were tested for their toxicity towards E. coli MG1655 using a high throughput screening method. Four biocompatible ionic liquids were then chosen with respect to their chemical structure and their capacity for styrene extraction was evaluated. All the investigated ionic liquids extracted close to 95% of the styrene present in the aqueous phase and achieved high distribution coefficients. Finally, styrene production using a previously metabolically engineered E. coli strain co-expressing PAL2 and FDC1 was performed in the presence of a selected phosphonium-based biocompatible ionic liquid, successfully achieving increased concentrations of styrene in comparison to the production in the absence of ionic liquid as a secondary extractant phase.